Regulation of bone homeostasis by MERTK and TYRO3 - Engelmann, Janik; Zarrer, Jennifer; Gensch, Victoria; Riecken, Kristoffer; Berenbrok, Nikolaus; Luu, The Vinh; Beitzen-Heineke, Antonia; Vargas-Delgado, Maria Elena; Pantel, Klaus; Bokemeyer, Carsten; Bhamidipati, Somasekhar; Darwish, Ihab S.; et al. (Nature Communications, 2022)
The fine equilibrium of bone homeostasis is maintained by bone-forming osteoblasts and bone-resorbing osteoclasts. Here, we show that TAM receptors MERTK and TYRO3 exert reciprocal effects in osteoblast biology: Osteoblast-targeted deletion of MERTK promotes increased bone mass in healthy mice and mice with cancer-induced bone loss, whereas knockout of TYRO3 in osteoblasts shows the opposite phenotype. Functionally, the interaction of MERTK with its ligand PROS1 negatively regulates osteoblast differentiation via inducing the VAV2-RHOA-ROCK axis leading to increased cell contractility and motility while TYRO3 antagonizes this effect. Consequently, pharmacologic MERTK blockade by the small molecule inhibitor R992 increases osteoblast numbers and bone formation in mice. Furthermore, R992 counteracts cancer-induced bone loss, reduces bone metastasis and prolongs survival in preclinical models of multiple myeloma, breast- and lung cancer. In summary, MERTK and TYRO3 represent potent regulators of bone homeostasis with cell-type specific functions and MERTK blockade represents an osteoanabolic therapy with implications in cancer and beyond.